THE INFLUENCE OF COMPETENCE AND REWARD PROVISION ON EMPLOYEE PERFORMANCE EFFECTIVENESS: (A Study on PTPN III Medan, HR Department) - Sihite, Fernando; Marpaung, Nicholas (Transpublika Publisher, 2024)
Employee performance is very necessary in working within the company, the importance of an employee's performance can affect the results of the work he does and also affect the goals of the company to be achieved. This study aims to analyze the effect of competence and rewards on the effectiveness of employee performance. The form of research used in this research is quantitative research with an approach. The research method used in this research is a quantitative research method with an association approach, the population in this study are PTPN III Medan HR employees with a total of 35 respondents, The primary data used was obtained by distributing questionnaires directly while the secondary data was obtained through a literature study. The data analysis method used is instrument test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that competency and reward had an effect on Employee Performance Effectiveness and the results of hypothesis testing simultaneously, obtained correlation coefficient values (R) of .888, which means that there is a relationship between Competency and Reward variables on Performance Effectiveness of 88.8% so that the relationship between these variables can be categorized as very close. While the Adjusted R Square value is .775 or the value of the determinant coefficient shows that the Competency and Reward variables on Performance Effectiveness are 77.5%, while the remaining 22.5% is influenced by other factors in outside of this research.